2022
DOI: 10.1039/d2fo01287a
|View full text |Cite
|
Sign up to set email alerts
|

Medicine–food herb:Angelica sinensis, a potential therapeutic hope for Alzheimer's disease and related complications

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease, which has brought huge burden to the world. Current therapeutic approach of One-molecule-one-target strategy fails to address the issues because of multiple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Accordingly, modern pharmacological studies gradually had realized ASR anti-inflammatory effect [4] such as therapeutic effect for hepatitis [5] and inflammation induced by subcutaneous, carrageenan or lipopolysaccharides (LPS) [6] , [7] . ASR contains a variety of plant active components, mainly including polysaccharides, ferulic acid (FA), amino acids and ligustilide (LIG) and so on [8] . FA (4-hydroxyl-3-methoxy-cinnamic acid) is a kind of phenolic acid, and it has the potential to be utilized in the field of food, pharmaceutical and biomedical industries due to its diverse physiological functions, such as antioxidant, antimicrobial and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, modern pharmacological studies gradually had realized ASR anti-inflammatory effect [4] such as therapeutic effect for hepatitis [5] and inflammation induced by subcutaneous, carrageenan or lipopolysaccharides (LPS) [6] , [7] . ASR contains a variety of plant active components, mainly including polysaccharides, ferulic acid (FA), amino acids and ligustilide (LIG) and so on [8] . FA (4-hydroxyl-3-methoxy-cinnamic acid) is a kind of phenolic acid, and it has the potential to be utilized in the field of food, pharmaceutical and biomedical industries due to its diverse physiological functions, such as antioxidant, antimicrobial and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 These phytochemicals have made DG play a vital role in its applications as a health food. 6 Moreover, DG has a wide range of pharmacological utilities, such as anti-inflammation, 9,10 antioxidation, 3,11,12 antibacterial, 13,14 anxiolytics, 15 antitumour, 16 anti-angiogenic, 17 detumescence, 18 and liver protection. 19 Besides in Asian countries, DG has also been exploited as a dietary supplement in women's care in Europe and America.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that DG herb consists of a large variety of volatile substances, 2 polysaccharides, 3 organic acids, 4 amino acids, 5 vitamins, 6 and microelements, 7 among others 8 . These phytochemicals have made DG play a vital role in its applications as a health food 6 . Moreover, DG has a wide range of pharmacological utilities, such as anti‐inflammation, 9,10 antioxidation, 3,11,12 antibacterial, 13,14 anxiolytics, 15 antitumour, 16 anti‐angiogenic, 17 detumescence, 18 and liver protection 19 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations